COMPARATIVE STUDY BETWEEN SOFTWARE TOOLS HELP DELUXE PC version 5.5 AND NORTON UTILITIES VERSION 4.5 ADVANCED EDITION - Hananto Kristono; Oon Amroni., Ir, MSc Oon Amroni., Ir, MSc (Jurnal Sistem Informasi, 1991)
Number of issues arising in connection with the efficiency and maintenance of a file / disk atlarge, and the development of computer technology along with its software, causing the softwarecan not be excluded anymore. Because so many types of assistive software available, in thispaper focuses on two research software that is very popular in Indonesia, namely PC ToolsDeluxe Version 5.5 and Norton Utilities Advanced Edition Version 4.5. Activities includesurveys and interviews conducted with several users who have enough experience in the use ofboth the software earlier. After obtaining the problem, gathered the abilities possessed by each ofthe software and compared. From the comparison results can be perceived advantages anddisadvantages of each, and should be used is unknown when Toos PC Deluxe 5.5 and when usedNorton Utilities Advanced Edition 4.5.